Constraints to unconventional livestock production - Peters, Kurt J. (German Foundation for International Development, 1986)
Discusses constraints, perspectives and problems in unconventional livestock production. Classifies unconventional livestock according to ecological distribution and body size. Lists promising unconventional livestock according to types and ecological distribution. Shows type of utilisation in unconventional livestock production in developing countries. Lists and discusses promising unconventional livestock species including camels, camelids, yak, banteng, water buffalo, eland and Oryx, deer, rabbit, capybara, guinea pig, cane cutter, guinea fowl, turkeys, ducks, pigeons, honey bees, silkworm moth, snails, ediblefrogs, and crocodiles & turtle.